Breaking barriers: An international perspective on preferences and challenges of tourists with disabilities - Zajadacz, Alina; Siwek, Matylda; Sowa, Paweł; Gonda, Tibor (Quaestiones Geographicae, 2026)
The fragmentation of national approaches underscores the need for international research to better understand the preferences and limitations of tourist travel for people with disabilities (PwD). This study, conducted between 2023 and 2024 on 1175 PwD across eight European countries, follows a standardised methodology under the Erasmus+ programme. It examines participation, preferences, and barriers in tourism based on disability type, providing a broader, cross-national perspective. The presentation of findings in multiple national languages ensures the inclusion of diverse PwD voices in the global discussion. The results highlight differences in endogenic and exogenic factors influencing travel decisions and experiences, as well as varying needs for support and accessibility solutions. Key conclusions emphasise the need for further research and action in three areas: barriers to travel differ by disability type; need for pre-travel support systems; and customised assistance and accessibility solutions. Beyond their academic value, these findings have significant practical implications for the tourism industry, supporting the development of more inclusive services, improving service quality, and enhancing market competitiveness.